Development of Poster Learning Media to Improve Learning Outcomes on the Main Material of Substances and Their Changes at SMP Negeri 5 Bengkulu City - Milla Rulisa; Adisel; Wiji Aziz Hari Mukti (EDUCATION JOURNAL OF INDONESIA, 2024)
This research aims to develop poster learning media on substances and their changes that are suitable and practical for use after being validated by several experts and responded to by several teachers and students. This research method uses the Borg & Gall development model which consists of 10 steps which the researcher will limit to 7 development stages, namely data collection , design/planning, initial product development, initial trials, product revisions, field trials, final product revisions. To create students who are more enthusiastic in participating in learning activities, the researcher de veloped this poster learning media to determine the feasibility of the poster learning media. Based on the results of data analysis after the product was validated by the validator, the resulting final product met the appropriate criteria with an average score from material experts of 96.42%, media experts of 92.15%, language experts of 78.15%, for teacher responses amounted to 84.10%, student response results were 97.5%. The results of field trials on students using poster media obtained an average student score of 84.8%. From the previous explanation, poster learning media is suitable for improving student learning outcomes. Keyword : Poster Media, Learning Results, Substances and Their Changes.